Greece and Nuclear Weapons: An Assessment - Kollaros, Panagiotis (HAPSc Policy Briefs Series, 2021)
This paper tries to answer the question on whether the acquisition of nuclear capabilities will serve the interest of the Greek state. The issue is approached by the exploration of Greek strategic constraints in correlation with the properties of nuclear weapons and the indexing and examination of the most important incentives and disincentives that influence a state’s decision to develop nuclear capabilities. Then, the Greek case is analyzed through the theoretical framework that was presented by Nuno P. Monteiro & Alexandre Debs in 2014, in order to examine if the process of developing weapons is a worthwhile endeavor based on its effects on Greek security. It is concluded that the development of nuclear weapons would serve the Greek interests, but there are practical reasons that render it nearly impossible for the foreseeable future.